Independent swarm grid vehicle charging by a logical DC-DC converter with hybrid boundary conduction mode - Karthikeyan Nagarajan; Kaliappan Esakkiappan; Dinakaran Kala Pandian; Dharmaprakash Ramasamy (Institute of Advanced Engineering and Science, 2023)
A modern and expanding civilization now takes for granted that future environments will be clean, efficient, and carbon neutral. Energy-efficient electrical loads, such as v ehicle charging now often u sed in schools, companies, and gated communities. Recent articles have focused more on Swarm smart grid technology as a way to transmit power from rooftop solar installations. A major issue with the system is the necessity for inverters and other conversio n equipment. The mechanism consumes part of the power generated by this process. It is possible to utilize the DC supply to power the v ehicle chargers in smart houses, although some tweaks may be necessary. The charging Vehicle is a common task that can sh are by different converter by swarm network. This study demonstrates the feasibility of using a swam nano grid t o interconnect buildings inside a campus or other large business or residential complex, as well as within a gated community. The electricity gr id is monitored by the swam nano grid system, which eliminates the need for costly equipment. The DC - DC converter was being controlled directly by the simple logic controller. M ATLAB Simulink simulates the controlled converter under load and shows the performance of a bidirectional DC-DC converter using waveforms.